Peran KPPU Mengawasi Persaingan Usaha di Sektor Pertambangan dalam Konteks Green Economy - Wulandari, Maria Mu'ti; Hidayat Jati, Baginda Khalid (Komisi Pengawas Persaingan Usaha, 2025)
ABSTRACT The mining sector plays a crucial role in Indonesia’s economy but faces challenges in ensuring fair competition and integrating green economy principles to support sustainable development. This study examines the role of the Business Competition Supervisory Commission (KPPU) in overseeing competition in the mining sector while promoting green economic practices. Using a normative juridical approach, the research analyzes relevant regulations and comparative studies on sustainable mining policies. The findings highlight that market concentration and regulatory fragmentation hinder competition and environmental sustainability. However, opportunities exist through policy reforms, fiscal incentives, and the adoption of international best practices, such as Finland’s green mining model. KPPU’s role can be strengthened by enhancing inter-agency coordination with the Ministry of Environment and Forestry (KLHK) and the Ministry of Energy and Mineral Resources (ESDM). The study concludes that integrating green economy principles into competition policies in the mining sector can enhance both market efficiency and environmental sustainability. The implications suggest that regulatory synchronization and cross-sector collaboration are essential to foster a competitive and sustainable mining industry in Indonesia. Keywords: Business Competition, Mining Sector, Green Economy, Sustainable Development